PERAN KOMUNITAS SOCIAL CORNER DALAM MENJADIKAN PEKANBARU SEBAGAI KOTA LAYAK PEMUDA - Cahyati, Aini Gustin; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
City Worth Youth (KLP) is an award event held by the Ministry of Youth and Sports to appreciate Youth Pledge Day. In the event the Social Corner was chosen as a community community in Pekanbaru City. The purpose of this study was to find out how the role of the Social Corner community in making Pekanbaru City a Youth-Friendly City. This research use desciptive qualitative approach. The subject of this study found 4 informants, namely 1 part of the Sports Division of the Pekanbaru City Dispora, the General Social Corner, the Secretary's Social Corner and 1 Social Member Corner. Data were collected through observation, interviews and documentation. The stages of data analysis are data reduction, data presentation, and drawing conclusions or levers. The results of this study indicate that the role of the Social Corner in youth awareness is as a facilitative role, namely as a forum for positive activities for youth. Furthermore, the role of the Social Corner in youth awareness is as an educative role, namely by campaigning for the dangers of drugs through social media. The educational role is participating in formal and informal education by holding teaching Social Corner activities. The role of the representative is to be a community representative in a youth-friendly city event and a visit to Batam. The Social Role of Corner in youth development is as a facilitative role, namely by developing entrepreneurship and conducting volunteer activities. The role of the representative is to be a community representative in a leadership training event held by KNPI Pekanbaru City and a visit to Bintan City. The educational role is to provide creative economic material. While the technical role is to conduct research in the village of Buluh Cina.Keywords: The Role of Community, A City Worth Youth